Environmental geochemical baseline determination and pollution assessment of heavy metals in farmland soil of typical coal-based cities: A case study of Suzhou City in Anhui Province, China. Issue 4 (April 2023) - Zhang, Jun; Peng, Weihua; Lin, Manli; Liu, Congmin; Chen, Song; Wang, Xiaojun; Gui, Herong
Abstract: Soil is the foundation of agricultural green development and human survival; the study of local environmental geochemical baselines can guide soil management and ensure the safe use of soil. In this study, a total of 100 shallow farmland soil samples were collected in each township of Yongqiao District, Suzhou City, Anhui Province, China. Herein, the contents of 10 heavy metal elements including As, Hg, Cd, Pb, Cr, Cu, Mn, Ni, Zn and Fe were determined. In addition, the geochemical baseline of heavy metals was calculated based on the relative cumulative frequency curve method, and the soil pollution status was evaluated. The results show that the average contents of As, Hg, Cd, Cu, Mn and Zn exceeded the soil background values of Anhui Province by 3.82%–64.74% (1.04–1.65 times), meanwhile, the average contents of Pb and Cr were lower than the soil background values of Anhui Province. The average contents of Cd, Cr, Cu, Mn and Ni exceeded the Chinese soil background values by 1.61%–64.74% (0.98–1.65 times). The geochemical baseline values of As, Hg, Cd, Pb, Cr, Cu, Mn, Ni, Zn and Fe were 9.585 mg/kg, 0.028 mg/kg, 0.112 mg/kg, 21.59 mg/kg, 53.66 mg/kg, 19.31 mg/kg, 543.8 mg/kg, 24.93 mg/kg, 50.57 mg/kg and 2.654%, respectively. The pollution assessment results also showed that most of the farmland soil samples in the study area were non-polluting or slightly polluted based on geochemical baselines. Hg and Cu in a few samples were moderately polluted, and Cd in only one sample was moderately intensely polluted. Combined with the distribution of pollution and field investigation, it is considered that Hg comes from atmospheric deposition and agricultural non-point source pollution of industrial pollution. Cu comes from animal husbandry and agricultural pollution. Meanwhile, Cd is related to natural sources, wood processing and agricultural fertiliser application. The study demonstrated that the calculation of soil geochemical background value should take full account of the differences between the various regions, combined with the current state, particularly the pre-consideration of the distribution of elements or pollutants. Then, reasonably select the evaluation standard value so that the evaluation results can truly reflect the state of soil pollution.